1980
DOI: 10.1021/jo01299a022
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric hydroformylation and hydrocarboxylation of enamides. Synthesis of alanine and proline

Abstract: gel, eluting the isomerically pure product with 20% acetonehexane: yield 1.833 g (61%); IR (neat) 1670,1645 (C=0) cm™1.The compound should be handled as 12a. Isomerization of Substituted Allylbenzenes (15a-c).Isomerization on 15a-c was effected in boiling toluene by using 2 as a catalyst and a substrate to catalyst ratio of 200.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…29 The less expensive chiral ligand (-)-DIOP was shown to be less efficient than the related ligand ( -)-DIPHOL as far as stereoselectivity is concerned: with the former ligand enantiomeric excesses up to 18% only were reached.27 N-Vinylphthalimide undergoes hydroformylation (50% conversion in 5 days) in the presence of Rh(I)/( -1-DIPHOL to yield the branched product almost exclusively, but in low ee (34.1%). Use of the [(-IDIPHOLlF't(SnC1,)Cl catalyst allowed a faster reaction with a higher ee (70%), but low aldehyde selectivity was obtained (57%) (Scheme 4).…”
Section: Cx-amino Acidsmentioning
confidence: 99%
“…29 The less expensive chiral ligand (-)-DIOP was shown to be less efficient than the related ligand ( -)-DIPHOL as far as stereoselectivity is concerned: with the former ligand enantiomeric excesses up to 18% only were reached.27 N-Vinylphthalimide undergoes hydroformylation (50% conversion in 5 days) in the presence of Rh(I)/( -1-DIPHOL to yield the branched product almost exclusively, but in low ee (34.1%). Use of the [(-IDIPHOLlF't(SnC1,)Cl catalyst allowed a faster reaction with a higher ee (70%), but low aldehyde selectivity was obtained (57%) (Scheme 4).…”
Section: Cx-amino Acidsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Applications that have been practiced at commercial scale include: polymer synthesis by co-polymerisation, methyl propionate synthesis by ethylene methoxycarbonylation and formation of racemic fine chemicals by hydroxycarbonylation of vinyl arenes (sometimes generated in situ from alcohols).…”
Section: Introductionmentioning
confidence: 99%
“…6 As part of a programme aiming to increase scope in this class of reaction, we have studied carbonylation of N-…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Klaus et al 8 have reported the cobalt-catalyzed selective hydroalkoxycarbonylation of enamides in the absence of chiral ligands. In the publication by Becker et al, 9 it is disclosed that only negligible optical yield (ca. 1%) was obtained in the asymmetric hydrocarboalkoxylation of Nvinylphthalimide.…”
Section: Introductionmentioning
confidence: 99%